1990
DOI: 10.1007/bf01292866
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of T20 indA ?PX to the reaction mechanism and relativistic effects

Abstract: A method for the analysis of interactions between fast deuterons and nucleons is developed, taking into account both the relativistic effects in the deuteron and the mechanism of their interaction. The inclusive proton spectra and the polarisation characteristics are investigated, taking for instance the fragmentation type processes of deuterons on nucleons. A strong sensitivity of the deuteron polarisation tensor component T2o both to the reaction mechanism and to the relativistic structure of the deuteron is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…In particular, secondary interaction in channels Ip1,3S 1 --3DI, and 3D 2 has a certain influence on the invariant cross section and corrects substantially the behaviour of the tensor asymmetry T20 in a medium energy region. We note here that similar conclusions have been made for the inclusive deuteron breakup at higher energies [5,6] and also for the processes of the deuteron electrodisintegration [25]. The strong influence of the second order graphs have been emphasized also in [13], where a different method of evaluation have been used.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…In particular, secondary interaction in channels Ip1,3S 1 --3DI, and 3D 2 has a certain influence on the invariant cross section and corrects substantially the behaviour of the tensor asymmetry T20 in a medium energy region. We note here that similar conclusions have been made for the inclusive deuteron breakup at higher energies [5,6] and also for the processes of the deuteron electrodisintegration [25]. The strong influence of the second order graphs have been emphasized also in [13], where a different method of evaluation have been used.…”
Section: Resultssupporting
confidence: 63%
“…Ignatenko and Lykasov [5] have presented calculations indicating that the pion production may be responsible for the deviations in the cross section. Later calculations [6] have also shown a considerable influence of corresponding triangle diagrams on T2o.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In reality, final state interactions and pion production alter significantly the interpretation of these experiments (see e.g. [208]). The polarization transfer from vector polarized deuterons to the fast protons has also been measured up to k ≃ 600 MeV/c.…”
Section: Hadronic Deuteron Break-up At High Energymentioning
confidence: 99%
“…Following this idea, the MS was often "forgotten" in different theoretical models; for example, in estimations of some reaction mechanisms beyond IA [16], model incorporation of quasi-free channels [17], reduced matrix elements in QCD [18], calculations within the Bethe-Salpeter formalism [19], contribution of quark exchange (QE) in the deuteron [20], etc. Direct calculations of MS effects in the DCS demonstrated that it does not change the universal A 2/3 dependence of the DCS and cannot explain experimental data without modification of the deuteron wave function (DWF) at short distances [2].…”
mentioning
confidence: 99%